NICKEL-BASED CATALYSTS FOR UREA ELECTROLYSIS: A REVIEW OF ELECTROLYSIS PERFORMANCE AND CATALYST DESIGN - Situmorang, Raja Doli Tota Parulian; Sujono, Hernandi; Jasmansyah, Jasmansyah; Murniati, Anceu; Hardian, Arie; Irwansyah, Ferli Septi (Walisongo Journal of Chemistry, 2025)
The increasing concentration of urea in wastewater poses both an environmental challenge and an opportunity for sustainable hydrogen production through urea electrolysis, which depends on efficient electrocatalysts. This review focused on nickel-based catalysts due to their high catalytic activity and stability in alkaline media. Using the PRISMA method, twenty studies published between 2020 and 2025 were analyzed based on current density, cell potential, Tafel slope, and stability. Through thematic analysis, catalysts were categorized according to their structure, composition, design strategy, and performance at 10, 50, 100, and 500 mA cm⁻². The review also highlights the importance of testing catalysts in real wastewater rather than in idealized electrolytes. An effective catalyst should exhibit a porous or layered nanostructure, multimetallic composition, and surface doping, while avoiding noble metals and overly complex architectures that hinder charge transfer and scalability.